A Small Story Concerning a Big Mistake: Returning Voice to a Breast Cancer Narrative - Martin, Elaine (Narrative Works, 2020)
This article arose from an error. In 2000, I began recording the story of myself and nine other university women with later stage breast cancer. Following the fifth death, I took on the task to make what I could of the archive. An introduction to Cathy Riessman and narrative research began to direct and support this work. Of major significance was the performative aspects of our storytelling, especially our vocality. Text and reason, not voice and utterance, is privileged in the academy, but still I committed to honouring vocality in telling our story. My initial attempts failed, but this paper begins the redress.